Effects of feeding elevated concentration of copper on prevalence and selection of fecal enterococci positive for transferable copper resistance gene in piglets - Amachawadi, Raghavendra G. (Kansas State University, 2010)
Copper, as copper sulfate, is often supplemented at elevated concentrations in swine diets, particularly in piglets, to promote growth. Growth promotional effects of copper are believed to be similar to that of antibiotics in that gut microbial flora is altered to reduce loss of nutrients and suppress pathogens. Bacteria exposed to copper may acquire resistance, and in Enterococcus faecium and E. faecalis, resistance is conferred by a plasmid-borne transferable copper resistance (tcrB) gene. The plasmid also carries macrolide [erm(B)] and glycopeptide (vanA) antibiotics resistance genes. The objectives of the research were to 1) determine the prevalence of tcrB gene in fecal enterococci of piglets in relation to normal (16.5 ppm) and elevated level (125 ppm) of copper supplementation, 2) determine the relationship of tcrB gene and susceptibilities to copper, erythromycin, and vancomycin, and 3) determine the transferability of tcrB gene in enterococci by conjugation. Weaned piglets, housed in pens, fed normal (16.5 ppm; control) or elevated level of copper (125 ppm) were used. Fecal samples were collected weekly for isolation of enterococci. Isolates were speciated by multiplex PCR and sodA gene sequence analysis. The prevalence of tcrB-positive enterococcal isolates was higher (P < 0.05) in the copper supplemented group than the control group. The prevalence of tcrB was affected by sampling days (P < 0.05) with a significant treatment and sampling time interaction (P < 0.05). The tcrB positive isolates were either E. faecium or E. faecalis, and majority of isolates was E. faecium. The mean MIC of copper for tcrB-positive isolates (21.1 mM) was higher (P < 0.001) compared to tcrB-negative isolates (6.1 mM). All isolates were resistant to erythromycin, tetracyclines and susceptible to vancomycin. The transferability of the tcrB gene from tcrB-positive strains to tcrB-negative strains was demonstrated by conjugation. The potential link between tcrB and antibiotic resistance genes and the propensity of enterococci to transfer tcrB to other strains suggests the possibility that copper supplementation may exert selection pressure for antibiotic resistance. The positive association between copper supplementation and prevalence of tcrB gene has important implications for antimicrobial resistance and food safety, which warrants further investigation.
Keywords: Antibiotic resistance; Copper supplementation; Piglets; tcrB gene; Enterococcus spp.; Biology, Microbiology (0410)